Hubungan Kontrol Diri dan Gaya Hidup dengan Perilaku Konsumtif pada Pekerja Pengguna E-Money di Jawa Timur - Yunus Diyati Ma'ruf; Rr. Amanda Pasca Rini; Bawinda Sri Lestari (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Among workers in East Java using electronic money, self-control appears linked to how much they spend. With digital payments growing fast, buying things takes less effort this ease might weaken restraint. A total of 259 individuals took part, chosen deliberately based on their use of e-payments. Instead of narratives or interviews, numbers shaped the findings here. Not random chance but careful selection guided who was included. What drives spending? One clue lies in how people manage impulses when tapping a phone to pay. Information came from surveys on self-regulation, daily habits, and spending patterns. Analysis shows people with stronger self-discipline tend to spend less impulsively when using electronic money. Those who place more value on lifestyle image show greater tendencies to engage in high consumption. Results suggest how personal habits shape financial choices in modern payment environments. What one prioritizes day to day may influence their impulse to buy just as much as willpower does.